2019
DOI: 10.1021/acsami.9b04680
|View full text |Cite
|
Sign up to set email alerts
|

Unique Scattering Properties of Silicon Nanowires Embedded with Porous Segments

Abstract: The development of advanced imaging tools is important for the investigation of the fundamental properties of nanostructures composed of single or multiple nanomaterials. However, complicated preparation processes and irreversible alterations of the samples to be examined are inevitable in most current imaging techniques. In this work, we developed a simple method based on polarization-resolved light scattering measurements to characterize the structural and optical properties of complex nanomaterials. In part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…[ 11,12 ] So far, 2D perovskites have been applied in solar cells, light‐emitting diodes (LEDs), photodetectors, and resistive memories. [ 13–20 ] Heterostructures often plays a vital role in these semiconductor devices. Thanks to its soft lattice, perovskite heterostructures can be conveniently prepared through anion exchange method.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11,12 ] So far, 2D perovskites have been applied in solar cells, light‐emitting diodes (LEDs), photodetectors, and resistive memories. [ 13–20 ] Heterostructures often plays a vital role in these semiconductor devices. Thanks to its soft lattice, perovskite heterostructures can be conveniently prepared through anion exchange method.…”
Section: Introductionmentioning
confidence: 99%
“…used a two‐steps vapor conversion method to synthesize 2D BA 2 PbBr 4 thin films with different grain sizes, from 180 nm to 30 µm by changing the transformation temperature from 100 to 200 °C. [ 167 ] When the grain size increases, the ON current remains almost the same, while the OFF current considerably decreases from 10 −4 to 10 −8 A. It was suggested that halide vacancies assisted filaments dominantly formed at the grain boundaries.…”
Section: Molecular‐level Low‐dimensional Halide Perovskite Memorymentioning
confidence: 99%
“…In 2019, Lee et al studied the effect of BA 2 PbBr 4 grain size on the performance of ITO/BA 2 PbBr 4 /Au memristors. [ 103 ] The BA 2 PbBr 4 films were formed by sequential vapor deposition, and the grain sizes were controlled by changing the transformation temperatures T T . When the T T values were 100, 150, and 200 °C, the grain sizes of BA 2 PbBr 4 were 180 nm, 1 µm, and 30 µm, respectively.…”
Section: Materials For Halide Perovskite Memristorsmentioning
confidence: 99%